2021
DOI: 10.1016/j.psj.2020.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between lipid source and vitamin A on broiler performance, blood parameters, fat and protein deposition rate, and bone development

Abstract: A total of 2622 male broilers were distributed in a 2 × 5 factorial design, using 2 lipid sources (soybean oil and palm fat), 5 levels of vitamin A supplementation (0, 3,000, 6,000, 12,000, and 24,000 IU kg −1 ), with 10 replicates, and also 1 control diet ( CD ) for each lipid source used (7 replicates), each experimental unit being composed of 23 birds. During the first 21 d (how were the birds fed) and from 22 to 42 d of age, a redistribution of the treatments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…In newborn Angers calves, injection of vitamin A significantly increased percentages of intramuscular fat (Harris et al, 2018). In broiler chickens, fat deposition rate was increased during 1-21 days after hatching but decreased during 22-42 days by dietary supplementation of vitamin A (Savaris et al, 2020). In the current study, in ovo injection of 300 nM atRA at E5-E7 resulted in an increase of weights and percentages of adipose tissues (Figure 3).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In newborn Angers calves, injection of vitamin A significantly increased percentages of intramuscular fat (Harris et al, 2018). In broiler chickens, fat deposition rate was increased during 1-21 days after hatching but decreased during 22-42 days by dietary supplementation of vitamin A (Savaris et al, 2020). In the current study, in ovo injection of 300 nM atRA at E5-E7 resulted in an increase of weights and percentages of adipose tissues (Figure 3).…”
Section: Discussionsupporting
confidence: 54%
“…In poultry, adipogenic differentiation in vitro can be induced by supplementation of atRA (Kim et al, 2020a,b;Lee et al, 2021). Dietary supplementation of vitamin A during early post-hatch period increased fat accretion in broiler chickens (Savaris et al, 2020). The present study aims to investigate the cellular effects of atRA on adipose growth in quail embryos as an animal model.…”
Section: Introductionmentioning
confidence: 97%
“…and C. perfringens co-infection, the serum cholesterol and uric acid contents were reduced in challenged birds. In the present study, the decrease in phosphorus and uric acid levels and increase in aspartate aminotransferase and creatine kinase activities induced with VitA supplementation indicated that excess VitA in the diet caused hepatic, cardiac and renal damage [ 29 ]. On the contrary, VitA supplementation increased serum low-density lipoprotein content regardless of NE challenge and reduced alkaline phosphatase activity in NE-challenged birds, which exhibited beneficial effects on lipid transportation and hepatobiliary function.…”
Section: Discussionmentioning
confidence: 97%
“…The possible mechanisms might be summarized as follows: First, vitamin A could indirectly improve bone health by restraining the excessive secretion of parathyroid hormone, a higher level of which was suggested to result in poor bone health [ 23 , 24 ]. Second, vitamin A can promote bone growth by means of affecting the growth hormone and stimulating the production of insulin-like growth factor 1, which are conducive to bone health [ 25 ]. Third, oxidative stress and reactive oxygen species can promote the development of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%